Penanganan Kerusakan Jalan Ditinjau Dari Rasio Manfaat-Biaya Bagi Pengguna Jalan (Road User Cost) Menggunakan Highway Development and Management (HDM-4) - Ahmad Royhan Mashuri Harahap; Eva Rita; Wahyudi P Utama (Universitas Batanghari Jambi, 2026)
The Muaro Kalaban–Kiliranjao national road in West Sumatra has deteriorated significantly, leading to higher road user costs such as increased fuel consumption, longer travel times, and greater accident risks. This study aims to assess the economic feasibility of road maintenance using the Highway Development and Management (HDM-4) model through the Benefit–Cost Ratio (BCR) approach. The analysis used data on Average Daily Traffic (ADT), International Roughness Index (IRI), vehicle operating costs, travel time costs, and accident costs. The simulation results show that in 2022 (BCR = 1.37), 2024 (BCR = 2.30), and 2025 (BCR = 5.50), maintenance scenarios are economically feasible since the BCR values exceed 1. Conversely, in 2021 (BCR = 0.93) and 2023 (BCR = 0.96), maintenance is not feasible as the BCR values are below 1. The most appropriate strategy is a combination of routine maintenance, rehabilitation, and reconstruction, which significantly reduces road user costs while extending pavement service life. Therefore, the application of HDM-4 proves effective as a decision-making tool in road maintenance planning.